The influence of government expenditure on economic growth in Ghana: An Ardl approach - Kwasi Poku; Emmanuel Opoku; Priscilla Agyeiwaa Ennin (Cogent Economics & Finance, 2022)
The relationship between public sector expenditure and economic growth for several decades past is still relevant today and continues to be a topic of debate among policy-makers and researchers. We examine the impact of government expenditure on economic growth in Ghana using data from 1970 to 2016, employing ARDL econometric estimation technique. The empirical findings indicate that, government expenditure has a positive relationship with economic growth in the short-run. The results further show that, Gross Capital Formation and Foreign Direct Investment show a significant positive relationship with economic growth in both the short-run and long-run. However, population growth reveals a significant negative relationship with economic growth (GDP Growth). We recommend government to increase public expenditure on profitable projects since it promotes economic growth.
Keywords: 330; ARDL; economic growth; Foreign Direct Investment; Ghana; government expenditure